Barriers to care for women with low-grade endometrial cancer and morbid obesity: a qualitative study. Issue 6 (27th June 2019) - Cusimano, Maria C; Simpson, Andrea N; Han, Angela; Hayeems, Robin; Bernardini, Marcus Q; Robertson, Deborah; Kives, Sari L; Satkunaratnam, Abheha; Baxter, Nancy N; Ferguson, Sarah E
Abstract : Objective: Obesity is a major risk factor for low-grade endometrial cancer. The surgical management of patients with obesity is challenging, and they may face unique barriers to accessing care. We completed a qualitative study to understand the experiences of low-grade endometrial cancer patients with morbid obesity, from symptom onset to diagnosis to surgery. Design: Semi-structured interviews were performed with endometrial cancer patients with morbid obesity (body mass index (BMI) > 40 kg/m 2 ) referred for primary surgery. Transcribed interviews were coded line-by-line and analysed using an interpretive descriptive approach that drew on labelling theory to understand patients' experiences. Thematic sufficiency was confirmed after 15 interviews. Setting: Two tertiary care centres in Toronto, Ontario, Canada. Participants: Fifteen endometrial cancer patients with a median age of 61 years (range: 50–74) and a median BMI of 50 kg/m 2 (range: 44–70) were interviewed. Results: Thematic analysis identified that (1) both patients and providers lack knowledge on endometrial cancer and its presenting symptoms and risk factors; (2) patients with morbid obesity are subject to stigma and poor communication in the healthcare system and (3, 4) although clinical, administrative, financial, geographic and facility-related barriers exist, quality care for patients with morbid obesity is an achievable goal. Conclusions: Improved education on the prevention and identification of endometrial cancer is needed for both patients and providers. Delivery of cancer care to patients with morbid obesity may be improved through provider awareness of the impact of weight stigma and establishing streamlined care pathways at centres equipped to manage surgical complexity.